The optimization of the overall performance of buildings - Silva, Sandra Monteiro (2008)
Building plan and shape are the result of a complex process. Functional, technical and aesthetic considerations all contribute to the building design. Wind, solar availability, shelter, exposure, air quality and noise conditions will affect the relationship between the building and its external environment and influence the shape and the design of the envelope. Materials selection, heating, cooling, daylighting, indoor air quality (IAQ), acoustic behaviour and energy strategies should be meshed at an early stage with the other requirements to ensure the buildings sustainability and overall comfort conditions. To accomplish this goal it is necessary to predict the thermal, acoustic, lighting and IAQ behaviour of the buildings, on the design phase, in order to be able to do the right choices, regarding, for instance the geometry, fenestration strategies, construction solutions and materials, to improve the occupants overall comfort and, simultaneously, to reduce the energy costs and increasing the sustainability of the buildings. So it is necessary to have an integrated approach to ensure the best overall behaviour taking into account all of the, sometimes incompatible, comfort and sustainability requirements. The aim of this study is to select a range of optimized solutions (envelope construction solutions, materials, fenestration and ventilation strategies, etc.), in order to improve the overall performance of buildings (comfort and sustainability).